Knowledge and practices of health care workers on medical waste disposal in Mapulaneng Hospital in the Ehlanzeni District of South Africa - Makhura, Ramadimetja Rosina (My University, 2016)
Background: Health care workers produce various types of waste in the course of rendering health care services. Each classification of waste must be disposed according to the prescribed guidelines. Improper disposal of waste may pose a danger to employees, patients and the environment. Health care workers must have adequate knowledge on disposal of medical waste. This study was therefore done to determine the knowledge and practices of health care workers on medical waste disposal. Objectives: This study aims to determine the knowledge and practices of health care workers on medical waste disposal at a hospital in the Mpumalanga Province in South Africa. Methods: A quantitative cross-sectional research approach was used at a regional hospital for the Mpumalanga Province in the Bushbuckridge Municipality under the Ehlanzeni District. The study respondents included professional nurses, enrolled nurses, enrolled nursing assistants, medical doctors, dental health and allied health staff. Data were collected through self-administered questionnaires analysed using International Business Management Statistical Package for Social Sciences 22 (IBM SPSS 22). Results: The results show that a high percentage of health care workers did not have adequate knowledge regarding disposal of medical waste but disposed medical waste appropriately. The results further show that knowledge and practice of health care workers had no association with age, gender and years of experience. There is an association between professional category and knowledge and practice of healthcare workers. Conclusion: Disposal of medical waste is the responsibility of all health care workers. There should be regular training of all categories of health care workers to improve their knowledge on disposal of medical waste and minimise the risks associated with improper waste management. This will further increase compliance with the guidelines of disposal of medical waste. Key words: Health care workers, medical waste, knowledge, practice, disposal
Thesis (MPH.) -- University of Limpopo, 2016.
Keywords: Medical waste; Disposal of medical waste; Medical wastes -- South Africa -- Mpumalanga; Health facilities -- Waste disposal -- South Africa -- Mpumalanga; Hospitals -- Waste disposal -- South Africa -- Mpumalanga; Waste management